Resolution of Local Head Election Disputes: The Urgency of Establishing a Special Court - Suparto Suparto; Admiral Admiral; Ardiansyah Ardiansyah; Jose Gama Santos (Faculty of Law, Universitas Slamet Riyadi, 2024)
In accordance with the Constitutional Court's decision Number 97/PUU-XI/2013, the Constitutional Court is no longer empowered to adjudicate disputes regarding regional election results, as Article 236 C of Law Number 12 of 2008 is deemed inconsistent with the 1945 Constitution of the Republic of Indonesia. In response to the Constitutional Court's ruling, Law Number 8 of 2015 was enacted, which designates a specialised judicial body as the authority for resolving disputes about regional head election results in Article 157. The objective of this study was to determine whether a state institution is suitable for adjudicating disputes regarding the outcomes of regional head elections in the future. This study employed a normative legal research methodology, utilising secondary sources and analysing them through qualitative descriptive techniques. The findings of this analysis indicate that the creation of a specialised judicial entity to adjudicate election result disputes is the optimal resolution to the legal issues that arise. To avoid generating additional issues with the establishment of new state organisations and to enhance efficiency, the body responsible for adjudicating disputes about regional head election outcomes would henceforth be Bawaslu. The present Bawaslu has evolved into an entity tasked with a specific judicial duty, namely adjudicating complaints about regional election results as stipulated in Article 157 of Law Number 10 of 2016 concerning the Election of Governors, Regents, and Mayors